Crystals for sustainability – structuring Al-based MOFs for the allocation of heat and cold. Issue 2 (25th July 2014) - de Lange, M. F.; Ottevanger, C. P.; Wiegman, M.; Vlugt, T. J. H.; Gascon, J.; Kapteijn, F.
Abstract : The special water adsorption behaviour of CAU-10-H makes it ideal for application in adsorption driven heat pumps and chillers. Abstract : Several Al-based MOFs of the CAU family have been investigated for application in the adsorption driven allocation of heat and cold. The special water adsorption behaviour of CAU-10-H makes it ideal for application in adsorption driven heat pumps and chillers. For increased performance, CAU-10-H crystals have been grown directly on both γ-alumina and metallic aluminium. Crystal growth on these surfaces can be controlled by the addition of acids.